Rodent hair is a Poor biomarker for internal manganese exposure. (November 2021) - Balachandran, Rekha C.; Yanko, Frank M.; Cheng, Pinjing; Prince, Lisa M.; Rivers, Chloe N.; Morcillo, Patricia; Akinyemi, Ayodele J.; Tabbassum, Sana; Pfalzer, Anna C.; Nie, Linda H.; Aschner, Michael; Bowman, Aaron B.
Abstract: Hair is used as a biomarker of manganese (Mn) exposure, yet there is limited evidence to support its utility to quantify internal vs external Mn exposure. C57BL/6 J mice and Sprague-Dawley rats were exposed in two blocks of 3 subcutaneous injections every 3 days starting on day 0 or 20. The control group received two blocks of saline (vehicle); Treatment A received the first block as Mn (50 mg/kg MnCl2 tetrahydrate), with the second block as either methylmercury (MeHg at 2.6 or 1.3 mg/kg) for mice or vehicle for rats; and Treatment B received Mn for both blocks. Hair was collected on days 0 and 60 from all treatment groups and Mn quantified by inductively coupled plasma-mass spectrometry (ICP-MS) and total Hg by Direct Mercury Analyzer (DMA). No correlation between internal Mn dose and hair Mn was observed, whereas hair Hg was significantly elevated in MeHg exposed vs non-exposed mice. Whole body Mn content at day 60 was quantified postmortem by neutron activation analysis, which detected significantly elevated Mn for Treatment B in mice and rats. Overall, we find no evidence to support the use of hair as a valid biomarker for internal exposure to Mn at a neurotoxic level. Highlights: Hair has potential to serve as a non-invasive biomarker for Mn exposure. Mice and rats received sub-cutaneous Mn injections to examine accumulation in hair. Whole body Mn was examined in mice and rats using NAA. Sub-cutaneous MeHg exposures confirmed as a positive control. No support for hair as a biomarker for internal Mn exposure at a neurotoxic level.